Clinical manual of sexual disorders - Balon, Richard; Segraves, R. Taylor 1941- (IG library, 2009)
Sexuality is an integral part of gender identity, self-image, and overall well-being. Sexual problems have a high prevalence in the general population and also among patients with mental disorders. Clinical Manual of Sexual Disorders is the first comprehensive text in decades to address the management and treatment of sexual dysfunctions.